In silico analysis of the Seven IN Absentia (SINA) genes in bread wheat sheds light on their structure in plants. - Jane Roche; Claire Guérin; Céline Dupuits; Cherkaoui Elmodafar; Pascale Goupil; Said Mouzeyar (PLoS ONE)
Seven IN Absentia (SINA) is a small family of genes coding for ubiquitin-ligases that play major roles in regulating various plant growth and developmental processes, as well as in plant response to diverse biotic and abiotic stresses. Here, we studied the SINA genes family in bread wheat Triticum aestivum which is a culture of major importance for food security worldwide. One hundred and forty-one SINA family genes have been identified in bread wheat and showed that their number is very high compared to other plant species such as A. thaliana or rice. The expansion of this family seems to have been more important in monocots than in eudicots. In bread wheat, the chromosome 3 distal region is the site of a massive amplification of the SINA family, since we found that 83 of the 141 SINA genes are located on this chromosome in the Chinese Spring variety. This amplification probably occurred as a result of local duplications, followed by sequences divergence. The study was then extended to 4856 SINA proteins from 97 plant species. Phylogenetic and structural analyses identified a group of putative ancestral SINA proteins in plants containing a 58 aminoacid specific signature. Based on sequence homology and the research of that "Ancestral SINA motif" of 58 amino acids, a methodological process has been proposed and lead to the identification of functional SINA genes in a large family such as the Triticae that might be used for other species. Finally, tis paper gives a comprehensive overview of wheat gene family organization and functionalization taken the SINA genes as an example.